ICT in the academic development of public universities in Metropolitan Lima and Callao in 2017 - Espinoza Marquez, Nataly Mircella (2019)
Objective: The research work is aimed at demonstrating that Information and Communication Technologies (ICT) contribute to the academic development of the public universities of Metropolitan Lima and Callao, with the aim of improving students' skills and knowledge in order to that in the future be competitive in their professional and work performance. Method: The type of research is descriptive and applicative, the non-experimental and transectional design was used, since a single period of time was analyzed. Likewise, the research work is correlational because there is a relation between the variables that were studied. The data were obtained from the surveys carried out on students and teachers of the different Public Universities of Metropolitan Lima and Callao, whose total sample corresponds to 246 people. Results: The reliability of the instrument was measured through the Cronbach's Alpha index whose value is 0.907, being a highly reliable value. The results expressed that information and communication technologies are influenced to the academic development of the public universities of Metropolitan Lima and Callao. Conclusions: It is concluded that information and communication technologies are directly related to the academic development of the public universities of Metropolitan Lima and Callao. The same ones that were validated with statistical tests applied.